Desenvolvimento de um instrumento para documentar a prática da dispensação de medicamentos prescritos - Santos, Sabrina Cerqueira (2018)
Introduction: the qualified practice of Dispensing is fundamental to the promotion of the rational use of medicines. Documentation is an indicator of quality and one of the essential steps in the care process. However, in Brazil there are no documentation models applicable to the practice of Dispensing. Objectives: to develop and validate an instrument to document the practice of dispensing prescribed medicines Methods: a methodological development study was carried out from February 2017 to October 2017, in two phases: (i) development of an instrument and (ii) content validation of the developed instrument. The development phase comprised three stages: (i) prototype development based on a systematic review; (ii) brainstorming and (iii) pre-Delphi. Subsequently, the validation process of the instrument content was performed through the Delphi technique. The instrument was sent to 40 experts, which all had overall experience in Dispensing, via the online platform Google Forms. The judges were instructed to evaluate the instrument according to the structure and content. Consensus was calculated using the Content Validity Index (CVI) and the items scored with CVI values >0.80. The present study was approved by the Ethics and Research Committee of the Federal University of Sergipe and all participants signed a Free and Informed Consent Term (TCLE). Results: the development stage generated three versions of the instrument: prototype; version 1 (changed after brainstorming) and version 2 (changed after pre-Delphi). In the content validation process of version 2 of the instrument, 23 experts returned their evaluation in the first round of Delphi (rate of return of 57.5%) and 17 in the second (rate of return of 73.9%). All items obtained IVC> 0.83, being considered validated. The final instrument comprised the following sections: general information, identification of technical and legal problems of prescription, conduct for the resolution of technical and legal problems of prescription, dispensed medicines, suspected drug related problem (DRP), verbal guidance, written guidance, routing and routing result. Conclusion: the instrument, developed and validated, presents the main variables that are provided in the Dispensing process. Thus, the proposed instrument can be useful to qualify this service and to improve the care process.